2021
DOI: 10.1111/obr.13269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on cardiometabolic health of adults with overweight or obesity: Focus on blood pressure, insulin resistance, and intrahepatic fat—A systematic review and meta‐analysis

Abstract: This systematic review examined the impact of exercise intervention programs on selected cardiometabolic health indicators in adults with overweight or obesity. Three electronic databases were explored for randomized controlled trials (RCTs) that included adults with overweight or obesity and provided exercise-training interventions. Effects on blood pressure, insulin resistance (homeostasis model of insulin resistance, HOMA-IR), and magnetic resonance measures of intrahepatic fat in exercise versus control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 114 publications
(188 reference statements)
3
35
0
Order By: Relevance
“…The uniqueness of this study, however, lay in including HIIT, alone or in combination with VLCHF diet, into consideration. An exercise intervention program proved to be effective in the treatment of insulin resistance in individuals with overweight/obesity ( 34 ), metabolic syndrome ( 35 ) or type 2 diabetes, i.e., reduces fasting insulin, HOMA-IR, fasting blood sugar, HbA1c, and body mass index ( 36 ). However, we did not show any or additional effect of HIIT on these variables after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The uniqueness of this study, however, lay in including HIIT, alone or in combination with VLCHF diet, into consideration. An exercise intervention program proved to be effective in the treatment of insulin resistance in individuals with overweight/obesity ( 34 ), metabolic syndrome ( 35 ) or type 2 diabetes, i.e., reduces fasting insulin, HOMA-IR, fasting blood sugar, HbA1c, and body mass index ( 36 ). However, we did not show any or additional effect of HIIT on these variables after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence concluded that exercise significantly improved patients' cardiometabolic health [45,46]. However, the effects of intradialytic exercise on cardiometabolic health remain limited, particularly involving Asian populations.…”
Section: Discussionmentioning
confidence: 99%
“…A murine study showed that maternal exercise can reduce western-style-diet (WSD)-induced obesity and improve hepatic lipid metabolism via activating the AMP-activated protein kinase ( AMPK ) and PPARγ -coactivator-1α ( PGC-1α ) signaling pathways [ 98 ]. Exercise-training intervention can also reduce intrahepatic fat accumulation, blood pressure, and insulin resistance in obese adults [ 99 ]. However, the working pressure and fast-food products make the change of lifestyle very difficult or cause most people to give up in this process.…”
Section: Treatment Options For Nafld and Nashmentioning
confidence: 99%